2016
DOI: 10.1007/978-1-4939-3609-0_21
|View full text |Cite
|
Sign up to set email alerts
|

The Consultancy Activity on In Silico Models for Genotoxic Prediction of Pharmaceutical Impurities

Abstract: The toxicological assessment of DNA-reactive/mutagenic or clastogenic impurities plays an important role in the regulatory process for pharmaceuticals; in this context, in silico structure-based approaches are applied as primary tools for the evaluation of the mutagenic potential of the drug impurities. The general recommendations regarding such use of in silico methods are provided in the recent ICH M7 guideline stating that computational (in silico) toxicology assessment should be performed using two (Q)SAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Currently, it is recognized that a successful drug is determined not only by better efficacy but also by acceptable absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties, leading to various in vitro high-throughput ADMET screening established in the early stages of drug discovery, which help reduce the cost of drug development and the number of safety problems ( Merlot, 2010 ; Moroy et al, 2012 ). Structure–activity/toxicity relationship has been employed to investigate ADMET properties and predict toxicity in silico ( Greene et al, 2015 ; Pavan et al, 2016 ; Guan et al, 2019 ). In addition, our recent studies have shown that structure–toxicity relationship combined with ADMET parameters evaluation and molecular docking (structure-based computations) can be used to predict drug impurity toxicity in silico ( Han et al, 2017 ; Han et al, 2018a ; Han et al, 2018b ; Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is recognized that a successful drug is determined not only by better efficacy but also by acceptable absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties, leading to various in vitro high-throughput ADMET screening established in the early stages of drug discovery, which help reduce the cost of drug development and the number of safety problems ( Merlot, 2010 ; Moroy et al, 2012 ). Structure–activity/toxicity relationship has been employed to investigate ADMET properties and predict toxicity in silico ( Greene et al, 2015 ; Pavan et al, 2016 ; Guan et al, 2019 ). In addition, our recent studies have shown that structure–toxicity relationship combined with ADMET parameters evaluation and molecular docking (structure-based computations) can be used to predict drug impurity toxicity in silico ( Han et al, 2017 ; Han et al, 2018a ; Han et al, 2018b ; Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of drug impurities is closely related to their structure. Structure-activity relationships (SARs) have been widely used in Europe and the United States to predict toxicity by computer (Greene et al, 2015; Pavan et al, 2016; Guan et al, 2019). We have recently systematically discussed the structure-toxicity relationship of cephalosporins via the zebrafish embryo toxicity test combined with computational chemistry and molecular docking techniques.…”
Section: Introductionmentioning
confidence: 99%